Winter storms [compact disc, unabridged] - Hilderbrand, Elin ([Winter Street trilogy, 2016)
Returning to prepare for Kevin and Isabelle's wedding, the Quinn family find themselves facing a powerful blizzard, holiday drama, and an emotional reunion.